Expression of LAG‐3 and efficacy of combination treatment with anti‐LAG‐3 and anti‐PD‐1 monoclonal antibodies in glioblastoma. Issue 12 (24th September 2018) - Harris‐Bookman, Sarah; Mathios, Dimitrios; Martin, Allison M.; Xia, Yuanxuan; Kim, Eileen; Xu, Haiying; Belcaid, Zineb; Polanczyk, Magdalena; Barberi, Theresa; Theodros, Debebe; Kim, Jennifer; Taube, Janis M.; et al.
Abstract : Like in many tumor types, immunotherapy is currently under investigation to assess its potential efficacy in glioblastoma patients. Trials are under way to assess the efficacy of new immune checkpoint inhibitors including anti‐PD‐1 or CTLA4. We here investigate the expression and efficacy of a novel immune‐checkpoint inhibitor, called LAG‐3. We show that LAG‐3 is expressed in human glioblastoma samples and in a mouse glioblastoma model we show that knock out or LAG‐3 inhibition with a blocking antibody is efficacious against glioblastoma and can be used in combination with other immune checkpoint inhibitors toward complete eradication of the model glioblastoma tumors. From a mechanistic standpoint we show that LAG‐3 expression is an early marker of T cell exhaustion and therefore early treatment with LAG‐3 blocking antibody is more efficacious than later treatment. These data provide insight and support the design of trials that incorporate LAG‐3 in the treatment of glioblastoma. Abstract : What's new? Glioblastoma derives some of its lethality from its ability to escape destruction by the immune system. Researchers have begun investigating immune checkpoint inhibitors as a tool to combat glioblastoma. Here, the authors report on a novel immune‐checkpoint inhibitor, LAG‐3. In a mouse model of glioblastoma, they successfully improved survival by eliminating LAG‐3, either by genetic knockout or using antibodies against it. They show that TILs from human glioblastoma samples express LAG‐3, and that high LAG‐3 expression correlates with reduced interferon release. The authors propose that anti‐LAG‐3, alone or in combination with other anti‐PD‐1 treatment, could improve glioblastoma treatment.